A new horizon in the treatment of biofilm-associated tonsillitis. (June 2014) - Ciftci, Zafer; Develioglu, Omer; Arbak, Serap; Ozdoganoglu, Tunis; Gultekin, Erdogan
Objective: To demonstrate the efficacy of tonsil brushing in patients with chronic tonsillitis to remove the microbial biofilm on the tonsil surface using an in vitro model. Design: Specimens from patients undergoing tonsillectomy were evaluated prior to and following surface cleaning methods, including rinsing and brushing, using scanning electron microscopy (SEM). Patients: The study population consisted of 25 randomly selected patients with chronic tonsillitis. Interventions: Specimens were collected and divided into four portions. Each portion received distinct surface cleaning methods and was immediately fixed for SEM examination. Outcome measures: The biofilm layer on the surface of the tonsils was examined using SEM. The density of the biofilm layer and the degree of persistence of the biofilm after rinsing and brushing were measured. Results: The surface biofilm of the tonsils in the first group, which were neither brushed nor rinsed, revealed a thick layer of biofilm on the mucosal surface. The second group of tonsils, which were only rinsed, also showed a thick layer of biofilm. The third group of tonsils, which were rinsed following gentle brushing using a soft toothbrush, showed a reduction in the thickness of the biofilm layer. The fourth group of tonsils, which were brushed with a hard brush, was almost devoid of a biofilm layer. Conclusion: Our results demonstrate that rinsing does not effectively remove the biofilm layer on the tonsil surface. The use of a harder brush was identified as a more powerful means of removing biofilm compared with a soft brush.